2010
DOI: 10.1159/000286839
|View full text |Cite
|
Sign up to set email alerts
|

Gross Appearance of the Ampullary Tumor Predicts Lymph Node Metastasis and Outcome

Abstract: Background/Aims: Patterns of lymph node involvement in carcinoma of the papilla of Vater (CPV) have not been studied in detail to date, and factors associated with lymphatic metastases and surgical outcome of this disease remain to be determined. Methods: Lymph node involvement and surgical outcome of 51 CPV patients were evaluated by extended lymphadenectomy specimens. Results: Lymph nodes with high metastatic potential were posterosuperior pancreaticoduodenal nodes (group 13a, 18%), posterior-inferior pancre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Determining whether or not tumor invasion is limited to mucosa before resection is very important, because patients with tumor invasion limited to the sphincter of Oddi may have nodal involvement. There have been some reports that patients with tumor invasion limited to the sphincter of Oddi did have nodal involvement [5, 9, 28, 29]. However, with regard to the extent of tumor invasion of the duodenum, it is impossible to completely discriminate between mucosa and the sphincter of Oddi even using EUS and IDUS preoperatively [20, 23, 25].…”
Section: Discussionmentioning
confidence: 99%
“…Determining whether or not tumor invasion is limited to mucosa before resection is very important, because patients with tumor invasion limited to the sphincter of Oddi may have nodal involvement. There have been some reports that patients with tumor invasion limited to the sphincter of Oddi did have nodal involvement [5, 9, 28, 29]. However, with regard to the extent of tumor invasion of the duodenum, it is impossible to completely discriminate between mucosa and the sphincter of Oddi even using EUS and IDUS preoperatively [20, 23, 25].…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, tumor size was not statistically significant (see results). A number of studies have also shown that tumor grade, stage, lymph node status and tumor size are important prognostic indicators which are closely and significantly associated with survival in these patients (Allema et al, 1995;Castro et al, 2004;Lazaryan et al, 2008;Morris-Stiff et al, 2009;Kayahara and Ohta, 2010;Qureshi et al, 2011;de Thomas and Ahmad, 2012). However, like in our study, tumor size was not seen to be significant in a study from Cleveland Clinic (Lazaryan et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The Whipple resection specimen includes the duodenum, head of pancreas, distal bile duct, and sometimes distal stomach. The following margins should be recognized and submitted for histopathologic examination when a specimen is received: common bile duct, pancreatic tissue, peripancreatic soft tissue and distal duodenal resection margins (Kayahara and Ohta, 2010). The pathological examination of Whipple resection specimens is important in evaluating multiple parameters which are prognostically important.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,17,18 Significant molecular biomarkers with prognostic and predictive value for patients' survival can guide additional treatment strategies, such as selecting patients for adjuvant therapy with the maximum therapeutic benefit or stratifying patients in a prospective study; they also help to optimize the chemotherapeutic regimen for individual patients. Unfortunately, such useful biomarkers have not been elucidated in patients with AC.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Unfortunately, randomized controlled trials, including the ESPAC-3 trial, 3 have revealed that a fluorouracil (FU)-based or a gemcitabine (Gem)-alone regimen shows only a modest benefit as the primary adjuvant chemotherapy for resected ACs. On the other hand, the addition of platinum compounds, such as cisplatin, to a Gem-based regimen demonstrated an improvement in the survival of patients with unresectable locally advanced or metastatic biliary tract cancer including AC.…”
mentioning
confidence: 99%